Jordan : A Whole New World - Price, Katie, 1978- (London Century, 2006)
Details what the author really made of her jungle experiences, the truth behind the romance with Peter Andre, her excitement over their new baby, the glamour behind their up-coming wedding, and more. This is the celebrity autobiography of the year that promises you the no-holes barred truth from the woman who loves to speak her mind
Include Color Illustration
Keywords: Models (Persons) -- Great Britain -- Price, Katie, 1978-